Taxation of cryptocurrencies and other cryptoassets: comparative analysis - La Rosa Almenara, Martín Alonso (2021)
In recent years, a new asset class is gaining momentum which emerged as a response to the economic crisis of 2008, the technology that is behind these assets depend on blockchain technology and cryptography, by using a decentralized network so the users of such networks can freely transfer value -using cryptocurrencies or crypto-assets, without having to depend on an intermediary that centralizes and registers all the transactions.This article analyses the current state of the taxation of cryptocurrency or crypto assets in Peru having as an initial reference point a recent study conducted by the OECD.